Status of care for end stage kidney disease in countries and regions worldwide: international cross sectional survey. (31st October 2019) - Bello, Aminu K; Levin, Adeera; Lunney, Meaghan; Osman, Mohamed A; Ye, Feng; Ashuntantang, Gloria E; Bellorin-Font, Ezequiel; Benghanem Gharbi, Mohammed; Davison, Sara N; Ghnaimat, Mohammad; Harden, Paul; Htay, Htay; et al.
Abstract: Objective: To determine the global capacity (availability, accessibility, quality, and affordability) to deliver kidney replacement therapy (dialysis and transplantation) and conservative kidney management. Design: International cross sectional survey. Setting: International Society of Nephrology (ISN) survey of 182 countries from July to September 2018. Participants: Key stakeholders identified by ISN's national and regional leaders. Main outcome measures: Markers of national capacity to deliver core components of kidney replacement therapy and conservative kidney management. Results: Responses were received from 160 (87.9%) of 182 countries, comprising 97.8% (7338.5 million of 7501.3 million) of the world's population. A wide variation was found in capacity and structures for kidney replacement therapy and conservative kidney management—namely, funding mechanisms, health workforce, service delivery, and available technologies. Information on the prevalence of treated end stage kidney disease was available in 91 (42%) of 218 countries worldwide. Estimates varied more than 800-fold from 4 to 3392 per million population. Rwanda was the only low income country to report data on the prevalence of treated disease; 5 (<10%) of 53 African countries reported these data. Of 159 countries, 102 (64%) provided public funding for kidney replacement therapy. Sixty eight (43%) of 159 countries charged no fees at the point of care delivery and 34 (21%) made some charge. Haemodialysis was reported as available in 156 (100%) of 156 countries, peritoneal dialysis in 119 (76%) of 156 countries, and kidney transplantation in 114 (74%) of 155 countries. Dialysis and kidney transplantation were available to more than 50% of patients in only 108 (70%) and 45 (29%) of 154 countries that offered these services, respectively. Conservative kidney management was available in 124 (81%) of 154 countries. Worldwide, the median number of nephrologists was 9.96 per million population, which varied with income level. Conclusions: These comprehensive data show the capacity of countries (including low income countries) to provide optimal care for patients with end stage kidney disease. They demonstrate substantial variability in the burden of such disease and capacity for kidney replacement therapy and conservative kidney management, which have implications for policy.